Penerapan Metode Pembelajaran Video Based Learning (VBL) Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fikih Di Madrasah Aliyah Al-Falah Branta Tinggi Tlanakan Pamekasan - Atik Arifana; Indra Nur Fitriani; Ach Mahfud; Nili Nili; Asari Asari (Institut Kariman Wirayudha Sumenep, 2022)
Video Based Learning is a learning method that uses recorded videos to assist in the learning process. Learning outcomes are a process of determining student learning outcomes through research activities or measuring learning outcomes. Knowing student learning outcomes is crucial to determine the level of success achieved by students after participating in learning activities. However, the facts that occur during learning, especially in class X MA Al-Falah Branta Tinggi Tlanakan Pamekasan in the subject of fiqh, learning outcomes are still far from the average value. This is caused by the use of methods that are still traditional and monotonous, such as the lecture method. The selection and application of methods are crucial for successful learning. During the learning process, students will not be bored if they use effective learning methods. The Video Based Learning method is one learning method that has the potential to arouse students' enthusiasm for learning. In this case, the video consists of two parts: visual and audio. Audio is used to convey information verbally, while visuals serve as the main source or presentation of content. This research is a qualitative descriptive study. The research subjects in this thesis were 33 class X MA Al-Falah Branta Tinggi Tlanakan Pamekasan students. Data collected through observation, interview and documentation process. This study aims to determine (1) the effectiveness of the application of the video based learning method and student learning outcomes in the subject of Fiqh class X MA Al-Falah Branta Tinggi Tlanakan Pamekasan (2) supporting and inhibiting factors in the application of the Video Based Learning method. The results of the research that the researcher has conducted are found that (1) The application of the Video Based Learning method is considered effective in improving learning outcomes, it can be seen from the learning outcomes of students in the subject of Fiqh Muamalah or Fiqh Transactions included in the good category, with the average value of students who reach the target that has been set. (2) supporting factors in the application of the Video Based Learning method are the enthusiasm and enthusiasm of students because they are helped by the presence of videos in understanding the material, while the inhibiting factors are the limited supply of tools, such as projector screens, laptops, etc., and require a lot of money, as well as the state of students who are tired when learning takes place